The effect of using (physical - skill) exercises in the circular style to develop the free throw skill of the national team basketball players on wheelchairs (Journal of the College of Basic Education, 2022)
The research aims to put exercises in the circular method to develop the free throw, and the extent of the effect of the physical-skill exercises of this method on controlling and controlling muscular work to develop the skill of the free throw. The researcher used the experimental method on a sample of the national team players for wheelchair football. The research sample, by the intentional method, included (16) players from the Iraqi national basketball team on wheelchairs, and after conducting tribal tests for them on (4) players from the national team, and exercises (physical - skill) were applied to the national team players, and their number was (12) players